Dom Helder Camara em verso e prosa: representações do bispo no universo artístico-literário. - Silva, Cícero Williams da (2023)
The crystallization of an individual's image in the social sphere is a phenomenon that requires time, and to comprehend it adequately, one must consider a series of actions that contribute to this process. In the case of Helder Camara, several episodes were responsible for his visibility in Brazil and worldwide; from his involvement in the 1930s with the Legion of Cearense Labor, the Catholic Female Workers' Union, and his affiliation with the Brazilian Integralist Action, to his role as a priest and assistant bishop in the 1940s and 1950s, respectively, in Rio de Janeiro, culminating in his appointment as the archbishop of Olinda and Recife in 1964, a position he held until 1985 – spanning precisely twenty-one years, coinciding with the period when Brazil was under a dictatorial regime. Concurrently, he traveled to various countries, delivering messages advocating for peace and the eradication of poverty to large audiences. Consequently, he became known both nationally and internationally, and his image was firmly consolidated. This study aimed to investigate a variety of artistic works produced from the second half of the 20th century to the present in which Dom Helder is represented as a character in the artistic-literary domain. The objective was to analyze how these works contributed to the consolidation of his religious and sociopolitical images. An exploratory study, the research required a bibliographical survey and the analysis of journalistic documents and primary sources. We drew upon literary theory to explore the character-building process and the application of the principle of verisimilitude in the realm of fiction. Furthermore, the concept of the representation of reality, as proposed by Erich Auerbach, was addressed. Finally, the study includes an analysis of the reception process of the works by the reader, considering the assumptions of reception aesthetics (RA) as outlined by Robert Jauss and Wolfgang Iser. We believe that this study contributes to the broadening of understanding regarding the life and work of Helder Camara, focusing particularly on the novel aspect of the recreation of his image in literary and fictional contexts.